The longitudinal association of remnant cholesterol with cardiovascular outcomes in patients with diabetes and pre-diabetes - Cao, Ye-Xuan; Zhang, Hui-Wen; Jin, Jing-Lu; Liu, Hui-Hui; Zhang, Yan; Gao, Ying; Guo, Yuan-Lin; Wu, Na-Qiong; Hua, Qi; Li, Yan-Fang; Li, Xiao-Lin; Xu, Rui-Xia; et al. (Cardiovascular diabetology, 2020)
Background The atherogenicity of remnant cholesterol (RC) has been underlined by recent guidelines, which was linked to coronary artery disease (CAD), especially for patients with diabetes mellitus (DM). This study aimed to examine the prognostic value of plasma RC in the patients with CAD under different glucose metabolism status. Methods Fasting plasma RC were directly calculated or measured in 4331 patients with CAD. Patients were followed for the occurrence of major adverse cardiovascular events (MACEs) and categorized according to both glucose metabolism status [DM, pre-DM, normoglycemia (NG)] and RC levels. Cox proportional hazards model was used to calculate hazard ratios (HRs) with 95% confidence intervals. Results During a mean follow-up of 5.1 years, 541 (12.5%) MACEs occurred. The risk for MACEs was significantly higher in patients with elevated RC levels after adjustment for potential confounders. No significant difference in MACEs was observed between pre-DM and NG groups (p > 0.05). When stratified by combined status of glucose metabolism and RC, highest levels of calculated and measured RC were significant and independent predictors of developing MACEs in pre-DM (HR: 1.64 and 1.98; both p < 0.05) and DM (HR: 1.62 and 2.05; both p < 0.05). High RC levels were also positively associated with MACEs in patients with uncontrolled DM. . Conclusions In this large-scale and long-term follow-up cohort study, data firstly demonstrated that higher RC levels were significantly associated with the worse prognosis in DM and pre-DM patients with CAD, suggesting that RC may be a target for patients with impaired glucose metabolism.